Environmental justice gaps in human-wildlife conflict research from a social-ecological systems perspective - Alba-Patiño, Daniela; Martín-López, Berta; Delibes-Mateos, Miguel; Requena-Mullor, Juan M.; Castro, Antonio J. (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Human–wildlife conflicts (HWCs) are increasingly prevalent and complex phenomena that often result in social tensions and environmental injustices. While the social–ecological systems (SES) perspective has been recently applied to understand the dynamics of HWC, little attention has been paid to how environmental justice is addressed in this field. This study presents a systematic review of 85 studies that analyse HWC using a SES lens, with the aim of examining to what extent these studies incorporate the three dimensions of environmental justice: distributive, procedural, and recognition justice. We assessed how social actors were identified, how benefits and cost were distributed, and how these actors were involved in both decision-making and research processes. Our findings reveal that most studies focused on mammals (58 %), and those human–human conflicts caused by human activities affecting wildlife populations and/or their habitats were the most frequently studied category (54 %). While local communities were commonly identified as social actors and resource losers, their participation in research was mostly limited to consultation, with few cases of collaboration or engagement. Moreover, the social actors identified as most affected by conflicts—those experiencing resource and livelihood losses—were not the same as those most involved in decision-making processes. These findings highlight the need to adopt more context-sensitive and justice-oriented approaches to address HWCs, enabling more equitable and effective conservation strategies. A social–ecological perspective helps to recognise the role of shifting social norms in conflict dynamics, while integrating environmental justice enables a deeper understanding of power imbalances.
Keywords: Human-human Conflict; Social-ecological System; Justice-oriented Approach; Conservation; Mammal